Onmyouji dan Peranan nya dalam Masyarakat Jepang di Tokyo Raven - Made Bramantya Yoga Saputra Made Bramantya Yoga Saputra; Wayan Nurita (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2026)
This study aims to describe Onmyouji and its role in Japanese society. This type of research is descriptive-qualitative. The data source used in this study is the Anime